Probabilistic design of sheet-metal die by finite element method - EKİCİ, BÜLENT (ELSEVIER SCI LTD, 2008)
In sheet-metal forming dies, highest stresses occur in bars which connect die to the frame. Considering fatigue behavior of bars with finite element method and probabilistic analyze provide many advantages predicting the life of dies in the design process. An effective and efficient design strategy is proposed to design sheet-metal die in order to reduce stress and increase fatigue life of sheet-metal die. In this strategy, finite element analysis, Approximate model, a numerical optimization algorithm and probabilistic design method Monte Carlo simulation are integrated to create an automated design tool. The reliability of the results are checked and refined by using probabilistic design techniques. Finally with the help of probabilistic design results, fatigue behaviors of the bars are predicted. At the end of the analysis process 43% volumes is gained. Stress value is 46.3% lower than the initial design. Safety factor of fatigue is reduced 36%. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: RELIABILITY; COMPONENTS